Laura Dassow Walls, Thoreau: A Life - Holt, Linda (Journal for the Study of Religion, Nature and Culture, 2018)
Laura Dassow Walls, Thoreau: A Life (Chicago: University of Chicago Press, 2017), 640pp., $35.00 (cloth), ISBN: 978-0-226-34469-0.